Faktor-Faktor yang Mempengaruhi Nisbah Bagi Hasil Nasabah pada Pembiayaan Mudharabah: Studi Kasus: KSPPS BMT Bina Ummat Sejahtera Pati - Sulisyanti, Ayu; Effendi, Jaenal (Lembaga Penelitian dan Pengabdian kepada Masyarakat of Universitas Islam Negeri Jurai Siwo Lampung, 2018)
Micro business is currently getting a share of the government and financial institutions because it has an important role in increasing the economic growth of the community. Currently the development of micro-enterprises faces several problems, one of which is limited capital, therefore KSPPS BMT BUS Pati was presented as a provider of financial services for micro-entrepreneurs. KSPPS BMT BUS Pati emphasizes the use of sharia principles in its contracts, one of which is the Mudharabah financing agreement. This contract is theoretically difficult to implement in terms of profit sharing, because capital must be fully from the capital owner and the possibility of moral hazard from related parties. This study aimed to determine the factors that influence the return on profit sharing. The research method used in this study is descriptive analysis and OLS. The results of the analysis show that the factors that influence the return of profit sharing practices at KSPPS BMT BUS Pati were the relationship between BMT and customers, business sector, financing amount, length of business, and payment period.